2021
DOI: 10.1186/s12872-021-02058-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of coffee consumption and CVD risk factors in elderly patients with T2DM

Abstract: Objective Clinical studies suggest increasing prevalence of cardiovascular disease (CVD) risk factors and diabetes among the elderly. Meanwhile, some food compounds, such as coffee, can also have beneficial effects on CVD risk factors. The aim of the present study was to examine the relationship between coffee consumption and CVD risk factors in the elderly with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study was performed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(67 reference statements)
1
4
0
1
Order By: Relevance
“…This result aligns with a study by Yamashita et al (2012), who reported no significant correlation between coffee consumption and fasting blood glucose levels (Yamashita et al, 2012). Contrary to these results, several other observational studies have shown that coffee consumption is significantly inversely correlated with fasting blood glucose or blood glucose levels 2 hours after an oral glucose tolerance test (OGTT) (Ghavami et al, 2021;Kabeya et al, 2022;Shin et al, 2019;Takami et al, 2013;Yarmolinsky et al, 2015). In theory, coffee consumption is related to the amount of bioactive content entering the body.…”
Section: Discussionsupporting
confidence: 88%
“…This result aligns with a study by Yamashita et al (2012), who reported no significant correlation between coffee consumption and fasting blood glucose levels (Yamashita et al, 2012). Contrary to these results, several other observational studies have shown that coffee consumption is significantly inversely correlated with fasting blood glucose or blood glucose levels 2 hours after an oral glucose tolerance test (OGTT) (Ghavami et al, 2021;Kabeya et al, 2022;Shin et al, 2019;Takami et al, 2013;Yarmolinsky et al, 2015). In theory, coffee consumption is related to the amount of bioactive content entering the body.…”
Section: Discussionsupporting
confidence: 88%
“…Baseline data were collected, including age, gender, race, body mass index (BMI), education, family income to poverty ratio (PIR), smoking status, alcohol (gm), cancer, hypertension, diabetes, the history of CVD medications ( 18 ), cholesterol, protein (gm), total fat (gm), carbohydrate (gm), estimated glomerular filtration rate (eGFR, mL/min/m 2 ), energy (10 kcal), coffee intake (cup/day), caffeine (100 mg), iced tea intake (cup/day), hot tea intake (cup/day), decaffeinated coffee, decaffeinated iced tea, decaffeinated hot tea. The NHANES asked all participants to provide some responses that had beverage consumption over the past 12 months ( 19 ); the survey question was “Did you drink coffee?” if your answer was yes, a follow-up question was asked “Did you drink how many cups of coffee, caffeinated or decaffeinated?” response options included <1 cup per day, 1–3 cups per day, ≥4 cups per day; then, they were asked “Did you drink decaffeinated, and how often do you drink decaffeinated coffee?” the choices in this question were, almost never, about a quarter to three quarters of the time, or always.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data were collected, including age, gender, race, body mass index (BMI), education, family income to poverty ratio (PIR), smoking status, alcohol (gm), cancer, hypertension, diabetes, the history of CVD medications (18), cholesterol, protein (gm), total fat (gm), carbohydrate (gm), estimated glomerular filtration rate (eGFR, mL/min/m 2 ), energy (10 kcal), coffee intake (cup/day), caffeine (100 mg), iced tea intake (cup/day), hot tea intake (cup/day), decaffeinated coffee, decaffeinated iced tea, decaffeinated hot tea. The NHANES asked all participants to provide some responses that had beverage consumption over the past 12 months (19); the survey question was "Did you drink coffee?"…”
Section: Data Collectionmentioning
confidence: 99%
“…En un estudio transversal realizado en 2017 con 300 pacientes diabéticos tipo 2, se evidenció que aquellos que tenían un consumo entre una y tres tazas al día de café tenían niveles de triglicéridos más bajos que aquellos que tomaban menos de una taza y más de tres al día (P = 0.036). En el mismo estudio, se encontró un aumento del HDL en la medida que aumentaba el consumo de café ( P= 0.034) (25). ON (Óxido Nítrico), LDL (Lipoproteína de Baja Densidad), PAS (Presión Arterial Sistólica), PAD (Presión Arterial Diastólica), AMPc (Adenosín Monofosfato Cíclico), FC (Frecuencia Cardiaca), GIP (Péptido Inhibidor Gástrico)…”
Section: Resultsunclassified